Ten little elves - "Brownlow , mike" (Orchard books; London., 2018)
Ten Little Elves is a festive, action-packed counting rhyme adventure designed for young readers. The story follows ten little elves on a mission to rescue Christmas. Along the way, they encounter a growling polar bear, a yowling yeti, and a scary Ice Queen. Children can count from ten to one and back again as the elves disappear and reappear, all while enjoying bouncy rhymes and spotting details on each page. The book features a sturdy board format with a super-sparkly cover, making it ideal for sharing together during the holiday season.